CONSTRUCTION OF SCIENTIFIC KNOWLEDGE THROUGH VERBAL INTERACTIONS IN THE CLASSROOM - Socha, Rosana Ramos; Dias Gomes Marin, Fatima Aparecida [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2015)
The present study is part of a Master's dissertation in Education, whose objective was investigate the verbal interactions between teacher and students in physics class. We search how those interactions can contribute in the construction of students' knowledge and present elements that drives to perception, by teachers, of the interactions that they live in classroom and the relevancy in the process of teaching and learning of them. This work consists of a qualitative research, whose data was obtained from observations and audio recordings of teacher's physics classes with a second year high school class. We verify that the teacher adopts a traditional methodology of teaching, which prizes presentation and explanation of contents without students has an active voice about the discussed subjects. We believe that the observed reality represents a larger universe. This means that rethink the physics teaching is necessary, with the purpose of realize interventions that qualify the process of teaching and learning.
Keywords: Verbal interaction; Physics teaching; Knowledge building